Intense Teaching Schedule in Israeli Teachers - Yaffa Buskila; Tamar Chen-Levi (Athens Institute for Education and Research, 2021)
The teaching profession is highly stressful. Stress is a negative phenomenon that develops under conditions of uncontrollable, prolonged and increased pressure. In this study, our goal is (a) to investigate teachers' perception of the sources of stress in school in light of the neoliberal reforms and (b) to compare these sources of stress in primary school, middle school and high school teachers. We hypothesize that the demands and the workload to improve scores in standardized tests, increase the need of teachers to take work home. Therefore, home demands may conflict with school demands. Furthermore, the greatest pressure is on elementary and middle school teachers: Early efforts to improve student achievements in the lower grades would result in better-prepared students in high schools. Data about the sources of stress is based on a previous study of Buskila, Buskila, Giris and Ablin (2019) that investigated the connection between the effects of stress on teachers on somatic syndromes. Three hundred and twenty-one public school teachers working in the Ministry of Education (MOE) in Israel participated in the study. Findings of the mean of the entire samples revealed that the highest level of stress was caused by intense teaching schedule with insufficient breaks. The second cause was related to the composition of the students in the class, and the third was home demands conflicting with school demands. In the middle schools, the highest levels of stress are caused by school principals (M=5.98, SD=3.09) and second is in high school (M=5.00, SD=3.33). The highest level of stress caused by the superintendent is on primary school teachers (M=3.97, SD=3.33) and the second are the middle school teachers (M=3.79, SD = 2.95). The lowest stress level was in high school (M=2.68, SD=2.83). Three significance differences of stress were found among primary, middle, and high schools: The school principal is the highest source of pressure in the middle schools (P=.034), and the superintendent causes the highest level of stress in primary schools (P=.006). The third cause was in high school, related to physical school conditions (p=.002). These results are relevant to teachers, educators, and policy makers involved in planning and managing educational strategies and teachers' schedules. Identifying and preventing the sources of stress can facilitate better teaching conditions, and a more effective and efficient atmosphere in school.